Smart Autonomous Trash Bin - Kerosi, Job; Mungai, David (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
It was conveyed that the rapid increase in population led to heightened sanitation- related issues and the current waste management systems exhibited deficiencies. In this research the challenge is addressed by proposing a Smart Autonomous Trash Bin. This bin is designed to open its lid only when a user approached and close automatically when the user moved away. It incorporates ultrasonic sensors to detect trash levels and data was transmitted through Bluetooth module to mobile app. If the trash exceeds a set threshold the bin does not open to prevent trash overflow and the mobile app indicates that the trash is full for trash collection. The system also employs servo motors to control lid movement based on user proximity. The mobile app facilitated waste collectors in identifying bins ready for collection and optimizing collection routes.